Editorial - Finlay, Linda (European Journal for Qualitative Research in Psychotherapy, 2018)
I am delighted to announce the re-launch of the online European Journal for Qualitative Research in Psychotherapy. It has not appeared since 2015, following the sudden death of Dr Ken Evans, the journal’s founder and senior editor. Now, generously hosted by the European Association of Integrative Psychotherapy (EAIP), the journal is back! This special inaugural volume is a commemoration of Ken Evans, who spent many years promoting psychotherapy in Europe. To celebrate his contribution, we offer Ken’s 2015 issue #8 once more (with some edits and updates) as Volume 8 (2018). Joanna Hewitt-Evans, Ken’s wife, has contributed her own introductory message to sit alongside this editorial and Ken’s original one.